Brazilian-Canadian Immigrant Businesses Configuration in the Greater Toronto Metropolitan Area, Canada - Machado, Michel Mott; Hossein, Caroline Shenaz; Falcão, Roberto Pessoa de Queiroz; Cruz, Eduardo Picanço (Frontera Norte, 2021)
The purpose of the present article is to examine self-employment and a sample of micro-enterprises of Brazilian immigrants in Toronto, Canada, and to unveil their social networking mechanisms, the influence of their culture, and human capital. The methodology encompassed the application of 74 questionnaires to Brazilian-Canadian entrepreneurs and 42 semi-structured interviews, aiming at understanding their experiences and relationships. The contributions include stating economic insecurity, political instability, and violence as reasons for migration and showing that social capital is essential for starting and developing a business as entrepreneurs often were driven out of necessity due to barriers in the labor market. As an exploratory study, the article is limited to discussing descriptive aspects of the Brazilian community of entrepreneurs. However, its implications might encompass new studies that involve creating migration policies for newcomers, longitudinal studies, or comparisons with other ethnicities.